2017
DOI: 10.1093/cid/ciw764
|View full text |Cite
|
Sign up to set email alerts
|

HIV Infection, Immunosuppression, and Age at Diagnosis of Non-AIDS-Defining Cancers

Abstract: Among PLWH, most cancers are not diagnosed at younger ages. However, this study strengthens evidence that lung cancer, anal cancer, and myeloma are diagnosed at modestly younger ages, and also shows younger ages at diagnosis of oral cavity/pharynx and kidney cancers, possibly reflecting accelerated cancer progression, etiologic heterogeneity, or risk factor exposure in PLWH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
64
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(74 citation statements)
references
References 30 publications
7
64
0
3
Order By: Relevance
“…A notable finding among African Americans in our study was the difference in age of young-onset prostate cancer diagnoses by HIV-infection status: age 50–54 years in HIV-negative subjects vs. 41–50 years in HIV-positive subjects (p=0.11). Although this difference in age at diagnosis was not statistically significant, several other studies also noted a trend toward younger age at prostate cancer diagnosis in HIV-infected compared to uninfected African American men (5, 1921). Further studies are warranted to evaluate whether HIV-infection status is associated with a younger age at prostate cancer diagnosis among men ages 40–55.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…A notable finding among African Americans in our study was the difference in age of young-onset prostate cancer diagnoses by HIV-infection status: age 50–54 years in HIV-negative subjects vs. 41–50 years in HIV-positive subjects (p=0.11). Although this difference in age at diagnosis was not statistically significant, several other studies also noted a trend toward younger age at prostate cancer diagnosis in HIV-infected compared to uninfected African American men (5, 1921). Further studies are warranted to evaluate whether HIV-infection status is associated with a younger age at prostate cancer diagnosis among men ages 40–55.…”
Section: Discussionmentioning
confidence: 62%
“…A recent study in the largest HIV cohort in North America found that while age at prostate cancer diagnosis was younger among HIV-infected subjects, the difference was not statistically significant (21); findings were inconclusive with respect to young-onset prostate cancer in groups by HIV status because age was examined in 10-year bins rather than comparing age of young-onset prostate cancer cases by HIV status. Young-onset prostate cancers diagnosed before age 55 are biologically and genetically distinct compared to prostate cancers diagnosed in older men (8, 22).…”
Section: Introductionmentioning
confidence: 99%
“…Shiels, M. S et al's findings supports our study, they found cancer that usually occur with advanced age to be occurring among young person's infected with HIV. (24) Crum-Cianflone, N had a contrary finding in their study, cancer in the HIV infected was associated with increasing age. (25) This could also be related to the age at which persons get infected with HIV in their setting.…”
Section: Discussionmentioning
confidence: 73%
“…1114 HIV increases the risk of lung cancer through mechanisms likely involving chronic inflammation, immunomodulation, and other infections. 11,1519 Lung cancer is the leading cause of cancer death among PLWH on ART, and is among the leading causes of death overall in this population.…”
Section: Introductionmentioning
confidence: 99%